Almost 9 Kilometres in Istanbul’s Newfound Land(scape) - Tümerdem, Nazlı; Medarić, Igor (Ecocene: Cappadocia Journal of Environmental Humanities, 2022)
On September 30, 1967, Robert Smithson went to the bus terminal in Manhattan, New York and boarded a bus heading northwest with a copy of the New York Times in his hands. He read the paper while commuting to his destination. He got off at Passaic, New Jersey where he performed a walk and took photographs of industrial sites that were seemingly mundane, uninteresting, and ubiquitous. Afterwards, he wrote ‘A Tour of the Monuments of Passaic, New Jersey’ which explains this experience. In this text, he referred to what he has photographed as ‘monuments.’ Our walk which was conducted in northern Istanbul on September 30, 2017 with the encouragement of Matthieu Duperrex , was performed as a tribute to Robert Smithson’s seminal text. Similar to Smithson, we roamed this landscape, photographed its monuments, and kept a walking log as a way to record this particular moment before it will transform irreversibly.